2008
DOI: 10.1103/physrevlett.101.076402
|View full text |Cite
|
Sign up to set email alerts
|

NovelJeff=1/2Mott State Induced by Relativistic Spin-Orbit Coupling inSr2IrO4

Abstract: We investigated electronic structure of 5d transition-metal oxide Sr 2 IrO 4 using angle-resolved photoemission, optical conductivity, and x-ray absorption measurements and first-principles band calculations. The system was found to be well described by novel effective total angular momentum J eff states, in which relativistic spin-orbit (SO) coupling is fully taken into account under a large crystal field. Despite of delocalized Ir 5d states, the J eff -states form so narrow bands that even a small correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

91
1,474
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,528 publications
(1,572 citation statements)
references
References 28 publications
91
1,474
5
2
Order By: Relevance
“…However, the origins of the unusual low temperature, abplane behaviour, is a more complex problem and remains an intriguing mystery in this compound, the details of which we continue to pursue. This c axis alignment of the magnetic moments is different to other layered perovskite iridates [17,18] reported to date, and may provide a unique insight into the dominant interactions responsible for the anisotropies in these systems.…”
mentioning
confidence: 62%
“…However, the origins of the unusual low temperature, abplane behaviour, is a more complex problem and remains an intriguing mystery in this compound, the details of which we continue to pursue. This c axis alignment of the magnetic moments is different to other layered perovskite iridates [17,18] reported to date, and may provide a unique insight into the dominant interactions responsible for the anisotropies in these systems.…”
mentioning
confidence: 62%
“…There have been a large number of reports along this direction [10], and we anticipate this field will continue to grow rapidly [11]. Because of the renewed interest in the relativistic spinorbit coupling (SOC) with correlations, iridium-based systems have started to attract significant interest [12].There have already appeared a number of theoretical predictions for novel phenomena [13][14][15][16] and experimental studies [17][18][19] using perovskite-type iridates. Recently, superlattices of SrIrO 3 (SIO) and SrMnO 3 (SMO) were epitaxially grown and their transport and magnetic properties were reported [20].…”
mentioning
confidence: 99%
“…There have been a large number of reports along this direction [10], and we anticipate this field will continue to grow rapidly [11]. Because of the renewed interest in the relativistic spinorbit coupling (SOC) with correlations, iridium-based systems have started to attract significant interest [12].…”
mentioning
confidence: 99%
“…Recently, the perovskite iridates have attracted much attention due to the formation of a novel J eff = 1/2 state associated with a large spin-orbital coupling (SOC) [1,2]. In order to explain the insulating ground state of Sr 2 IrO 4 , Kim et al [1] proposed that the strong SOC splits the otherwise broad t 2g band of the octahedral-site, low-spin Ir 4+ (5d 5 ) array into a filled, low-energy J eff = 3/2 quartet band and a half-filled, high-energy J eff = 1/2 doublet band, which can open a Mott gap by a moderate on-site Hubbard U, leading to a novel SOC-driven Mott insulating state.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain the insulating ground state of Sr 2 IrO 4 , Kim et al [1] proposed that the strong SOC splits the otherwise broad t 2g band of the octahedral-site, low-spin Ir 4+ (5d 5 ) array into a filled, low-energy J eff = 3/2 quartet band and a half-filled, high-energy J eff = 1/2 doublet band, which can open a Mott gap by a moderate on-site Hubbard U, leading to a novel SOC-driven Mott insulating state. Moon et al [3] further demonstrated that a bandwidth controlled insulator-to-metal transition can be realized in the Ruddlesden-Popper series Sr n+1 Ir n O 3n+1 (n = 1, 2, ) with increasing the number of perovskite layer n. In contrast to the former two compounds, Sr 2 IrO 4 (n = 1) and Sr 3 Ir 2 O 7 (n = 2), which are magnetic insulators, less attention has been paid to the SrIrO 3 (n = ) perovskite, presumably due to the fact that the bulk sample can only be stabilized under high-pressure and high-temperature conditions [4].…”
Section: Introductionmentioning
confidence: 99%